From Policy to Pedagogy: Religious Moderation as a Counter-Radicalization Strategy in Islamic Education — A Systematic Literature Review - Prasetyo, Gatot; Fauziah, Yanuar Rizki; Syafii, Ahmad (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study maps current evidence on religious moderation in Islamic Education in Indonesia to assess the effectiveness of policy, curriculum, pedagogy, and the institutional ecosystem—framed by Pancasila—as a counter-radicalization strategy and a shaper of inclusive character. Design/methods/approach – Systematic Literature Review (SLR) grounded in Kitchenham & Charters. Scopus search (February 12, 2025) using TITLE-ABS-KEY(